ANALISIS KONFLIK DALAM ORGANISASI: TINJAUAN LITERATUR TERHADAP KONSEP, JENIS, DAN SUMBER KONFLIK - Fauziah Nur Azira; Winda Claudia Situmorang; Octa Nazilla Rahmadani; Yudo Handoko (STKIP Subang, 2026)
Through a thorough literature review focusing on concepts, categories, and their origins, this study aims to examine organizational conflict. Differences in interests, views, values, and communication between individuals or groups within an organization lead to unavoidable organizational conflict. Scientific books, publications, and related academic materials from recent years were analyzed using qualitative literature review techniques in this study. According to the results, conflicts in an organization can be seen from various conceptual perspectives, classified into several categories such as task conflict, relationship conflict, and process conflict, and originate from various causes, including resource limitations, individual differences, structural problems, and communication disruptions. In addition, this study shows that, when managed effectively, conflict can have beneficial effects such as promoting creativity, critical thinking, and improved decision-making, but if not handled properly, it can have detrimental consequences on organizational performance. To maximize organizational dynamics and achieve organizational goals, efficient conflict management techniques are therefore required. By offering a theoretical framework for understanding conflict and emphasizing the need for its strategic management within organizations, this study contributes to our understanding of it.